El 'juego-rima' de origen hispánico en Argentina hoy. Un primer acercamiento - Pérez, Soledad; Ruiz, Monica (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2012)
This essay attempts at a new appreciation of the female children's "rhyme-game", in the River Plate area, as a means of survival of the Romancero as well as other compositions from Spanish origin, which are transmitted orally. The chosen approach aims at the crossing of fieldwork results with bibliographical -Spanish as well as Argentinean- information that compiles several types. The analysis of our findings allows us to conclude that this genre, which was transplanted with immigration, continues to be updated and permits the conservation of types that were transmitted for generations in both places